Etnoparenting Influences the Moral and Religious Development of Early Childhood among Transmigrant Community - Leli Fertiliana Dea; Zulkipli Lessy; Sigit Purnama (COUNS-EDU: The International Journal of Counseling and Education)
This study examines ethnoparenting and its role in the moral and religious development of early childhood in the Sundanese transmigrant community in East Lampung. Using a qualitative case study approach, data were collected through participatory observation, in-depth interviews, and document analysis in Sukadana Baru Village, Gerem Cempaka Hamlet. Findings reveal that Sundanese cultural values—such as hospitality, cooperation, and respect for elders—are deeply embedded in daily parenting practices. Ethnoparenting significantly shapes children's morality and religiosity, fostering respect for parents and active participation in religious activities. However, modernization and social changes present challenges to maintaining these values. Despite these obstacles, the community continues to integrate cultural traditions into parenting to ensure their preservation for future generations.